Influence of polyethylene glycol on the properties of TiO2 films by Squeegee method - M.F. Malek, A.S. Ismail, M.M. Yusoff, R. Mohamed, M.K. Ahmad, M. Rusop, (Universiti Pendidikan Sultan Idris, 2016)
Influence of polyethylene glycol on the properties of TiO2 films by Squeegee method by M.F. Malek, A.S. Ismail, M.M. Yusoff, R. Mohamed, M.K. Ahmad, M. Rusop,